'Like a prison without bars': Dementia and experiences of dignity. (December 2013) - Heggestad, Anne Kari T; Nortvedt, Per; Slettebø, Åshild
The aim of this article is to investigate how life in Norwegian nursing homes may affect experiences of dignity among persons with dementia. The study had a qualitative design and used a phenomenological and hermeneutic approach. Participant observation in two nursing home units was combined with qualitative interviews with five residents living in these units. The study took place between March and December 2010. The residents feel that their freedom is restricted, and they describe feelings of homesickness. They also experience that they are not being seen and heard as individual autonomous persons. This lack of freedom, experiences of homesickness and feelings of not being confirmed and respected as individual autonomous persons may be a threat to their personal dignity. In order to protect and enforce the dignity of persons with dementia living in nursing home, we should confirm them as whole and as individual persons, and we should try to make the nursing homes less institutional and more home like.